Preferential and Non-Preferential Approaches to Trade Liberalization in East Asia: What Differences Do Utilization Rates and Reciprocity Make? - Jayant Menon (Asian Development Bank (ADB), 2013)
Previous studies on the impacts of free trade agreements (FTAs) in East Asia have assumed full utilization of preferences. The evidence suggests that this assumption is seriously in error, with the estimated uptake particularly low in East Asia. In this paper, we assume a more realistic utilization rate in estimating impacts. We find that actual utilization rates significantly diminish the benefits from preferential liberalization, but in a non-linear way. Reciprocity is an important motivation for pursuing FTAs over unilateral actions, although the Doha Round could deliver the same outcome if only it could be concluded. We isolate the impact of reciprocity, but find that the additional benefits also depend on utilization rates. Furthermore, the potential for trade deflection combined with possible retaliatory actions could negatively affect members and non-members. In the absence of Doha, the multilateralization of preferences, even without reciprocity, is the practical route that is most likely to deliver the greatest benefits to members. Global liberalization, while difficult to attain, would maximize world welfare while posing no risk in its realization.
hdl:11540/2095
Keywords: F13; F14; F17; 330; Unilateralism; multilateralism; regionalism; FTA; reciprocity; utilization rates; CGE models; Handelspräferenzen; Freihandelszone; Handelsliberalisierung; CGE-Modell; Allgemeines Gleichgewicht; Ostasien